Comparative Analysis of Bar Associations and Law Societies in Select European Jurisdictions - Said, Agnes (World Bank, Washington, DC, 2017)
As some of European Union’s (EU’s) neighboring countries are about to embark on EU accession negotiations, they are looking to reform their justice systems to align them with EU standards. This report on the role and powers of bar associations in selected EU member states (old and new EU members), and candidate countries has been drawn up with the purpose of informing the relevant policy process in those countries. Bar associations play a fundamental role in regulating and ensuring the efficiency, quality, and access of legal services to citizens and businesses. This report focuses on select aspects and powers of bar associations, namely: the bar and the legal profession; what are the conditions for entrance to the bar; the decision-making bodies of the bar, their competences, and relation; administrative capacities of the bar and services they are providing; inter-bar relations in countries where there are several bar associations; the fee structure for lawyers and fees in general; fees for legal aid and mandatory defense and their structure; complaints mechanisms against lawyers who are members of the bar; disciplinary procedure and measures against lawyers; and external supervisory power over the bar. The countries selected for the comparative analysis are: Albania, Austria, Bulgaria, Croatia, Czech Republic, England and Wales, Lithuania, the Netherlands, Serbia, and Spain. This analysis was conducted from May 2016 to January 2017, based on desk research, interviews with Council of Bars and Law Societies of Europe (CCBE), a questionnaire completed by the relevant national bar associations (with the exception of Serbia), and consultations organized by CCBE in September 2016.